COVID-19 aerosols and droplets and their entry into lung alveoli - Sheldon Weinbaum; Bingmei Fu; Herbert G Kayser (Archive of Biomedical Science and Engineering - Peertechz Publications, 2020)
We have been asked by friends, many who are not scientists, how far droplets from a sneeze, cough or breathing travel before they disappear largely through evaporation or just simple settling in an indoor environment. Basically, how does the virus spread in indoor environments and how effective are masks. Which particles penetrate deep into your lungs, and why do your lung capillaries become leaky? These are not simple questions because they depend on temperature, relative humidity and most importantly the initial size of the droplet or aerosol. Where does the 6 feet separation distance come from?